Effect of physical activity interventions on quality of life in older adults: A protocol for systematic review and meta-analysis. Issue 48 (2nd December 2022) - Lamberti, Nicola; Manfredini, Fabio; Babjaková, Jana; Gallè, Francesca; Medijainen, Kadri; Karatzaferi, Christina; Pavlova, Iuliia; Netz, Yael; López-Soto, Pablo Jesús
Abstract : Introduction: Quality of life (QoL) has been acknowledged as a fundamental concept in the field of health and is favorably improved by physical activity (PA). This systematic review aims to assess the benefits and harms of different types of PA to improve health-related QoL in both community-dwelling and diseased older adults to provide a recommendation for the minimum amount of PA needed to obtain measurable QoL benefits. Methods and analysis: We will search MEDLINE, Cochrane Central Register of Controlled Trials, CINHAL, Epistemonikos, Web of Science and gray literature. Randomized controlled trials enrolling healthy or diseased older adults aged > 65 years, providing any kind of physical activity intervention and having quality of life as an outcome will be included. There will be no language restriction. Two independent reviewers will screen the papers, and a third reviewer will resolve the conflicts. The quality of the included studies will be assessed through the Risk of Bias 2.0 tool. Finally, data will be extracted to create proper meta-analyses of comparisons between the different kinds of physical activity interventions or to control groups. Ethics and dissemination: This review does not require approval from the Ethics Committee. The results will be disseminated in peer-reviewed journals and at international conferences; moreover, the findings will be shared on social media using an accessible language.